Socio-economic differentials in child stunting are consistently larger in urban than rural areas: analysis of 10 DHS data sets - Menon, Purnima; Ruel, Marie T.; Morris, Saul Sutkover (International Food Policy Research Institute, 2000)
Urban-rural comparisons of childhood undernutrition suggest that urban populations are better-off than rural populations. However, these comparisons could mask the large differentials that exist among socioeconomic groups in urban areas. Data from the Demographic and Health Surveys (DHS) for 11 countries from three regions were used to test the hypothesis that intra-urban differentials in child stunting were greater than intra-rural differentials, and that the prevalence of stunting among the urban and the rural poor was equally high. A socioeconomic status (SES) index based on household assets, housing quality, and availability of services was created separately for rural and urban areas of each country, using principal components analysis. In most countries, stunting in the poorest urban quintile was almost on par with that of poor rural dwellers. Thus, malnutrition in urban areas continues to be of concern, and effective targeting of nutrition programs to the poorest segments of the urban population will be critical to their success and cost-effectiveness.